USING âMOST NAMESâTO IMPROVE STUDENTSâ SPEAKING SKILL IN DESCRIPTIVE TEXT - Rini, Heny Sulistyo (English Teaching Journal, 2013)
The research was done in August 2012 in SMPN 1 Geger Madiun. The subject of the study was the eight year students consisting of 20 students. It was a classroom action research. The researcher conducted the research in some steps for each cycle. There were planning, acting, observing, and reflecting. In collecting data, there were two kinds of data which were used in this study, the quantitative data and the qualitative data. The quantitative data were in the forms of studentsâ scores. The data were studentsâ scores from the beginning of the research to the end of the research. They came from the tests given. The qualitative data were collected by the following techniques: observations, interviews, and document analysis. The quantitative data were analyzed using descriptive statistics. It compares the score of the pretest to the score of the post test. The qualitative data were analyzed into data reduction, data display and conclusion drawing/ verification.The research findings showed that by implementing the âMost Namesâ in the speaking class, there were some improvements which can be classified into three main points as follow: The improvement of studentsâ speaking skill; The improvement of studentsâ participation; The improvement of studentsâ interest; And the improvement of studentsâ motivation. For that reason, âMost Namesâ was able to stimulate students to speak English.In conclusion, âMost Namesâ is able to improve studentsâ speaking skill in class VIII/A. However, âMost Namesâ has its own strength and weaknesses. Most Names stimulated students to be more active, interactive, and creative to speak English.In short, it is recommended to the teachers to use âMost Namesâ to improve the studentsâ speaking skill in English.Key words: Most Names, Speaking, Descriptive